Pengaruh pemberian beberapa jenis pakan pada pertumbuhan ikan kerapu Cantang Epinephelus sp di Karamba Jaring Apung di Teluk Talengen Kepulauan Sangihe - Tumadang, Liswara S.N.; Sampekalo, Julius; Lantu, Sartje (Universitas Sam Ratulangi, 2016)
The research was conducted in floating net cage for at Talengen Island Sangihe to study the growth of grouper (46-70 g in average) fed various type of feed including fish flesh, pellet, cassava, sago) for six weeks, and to determine the food conversion ratio of each food type. The treatments consisted of A (fish flesh), B (fish flesh + cassava), C (fish flesh+sago), D (pellet). Fish was culture in 12 floating net cages measuring 1x1x1,5 m each, 10 fish/cage. Research results showed that the highest weight gain was achieved in fish in treatment C (87.6%), followed by treatment A (76.1%) , B (69.8%), and D (52.5%).Â Statistically, treatment C was significantly differentÂ compared to treatment A, B and D. The use of fish flesh combined with sago was able to improve growth of grouper Kata kunci : Kerapu Cantang,Â growth, food conversion ratio, floating net cage